Late Archean tectono-magmatic evolution of the central Slave Province, Northwest Territories - King, J. E.; Davis, W. J.; Relf, C. (Canadian Journal of Earth Sciences, 1992)
An early tectono-stratigraphic and late plutonic assemblage are distinguished in the central part of the Archean Slave Province (Contwoyto Lake area) on the basis of their relationship to deformation and metamorphic episodes, and by geochemical characteristics. The older assemblage, which predates the onset of intense deformation and the thermal peak of metamorphism, comprises 2.68–2.65 Ga calc-alkaline volcanic and plutonic rocks, as well as extensive turbidites. The younger assemblage comprises ca. 2.61–2.58 Ga plutonic units that were emplaced during and after deformation (D,–D 3 ) and the thermal peak of metamorphism. Compositions of the late plutonic units vary systematically with time of intrusion from an early, calc-alkaline, diorite – tonalite suite to late peraluminous granites. The early assemblage is interpreted to represent remnants of an island arc (or arcs) overlain by turbidites and accreted during D 1 and D 2 . The later assemblage is interpreted as a product of late- to post-accretion, suprasubduction-zone magmatism and associated crustal melting.